IMPROVING STUDENTS’ READING SKILL THROUGH CONCEPT SORT STRATEGY - Candra Febriyanto (English Education Department Slamet Riyadi University Surakarta, 2018)
Reading is not only read activity, but also understanding meaning of the word in the text. Reading is one of four skill in English. Reading skill is one skills that should be mastered by students in all levels of schools. In this study there are two objectives: To find out whether Concept Sort Strategy can improve reading skill and to identify how the condition when Concept Sort Strategy (CSS) is implemented in Reading class at the Eight Grade of SMP N 4 Sukoharjo in Academic Year 2017/2018. Concept Sort Strategy is strategy to introduce and organize concepts and examples to introduce the students examples of sorting the word of the material in their class directly. The researcher used Classroom Action Research which was carried out from November 2017 to February 2018. The researcher used observation, interview, document, and test to colleting the data. The result of this research showed that there was improvement in students’ Reading skill. Based on the mean score of the students in pre-test was 29.65, in post-test 1 the mean score increased to 61, in the post-test 2 the mean score was increased to 72.78. The result from pre-test and post-test 1 was significance which 2.040 < 11.9 > 2.744. Then t-test result between post-test 1 and post-test 2 were 2.040 < 6.5 > 2.744. According to the result, it can be concluded that Concept Sort Strategy was appropriate to improve the students’ reading skill. Besides that, the condition of the class were more active and the students more interest with the strategy. Keywords: Reading Skill, Concept Sort Strategy (CSS), Classroom ActionResearch